Challenges Faced by Students in Open and Distance Mode of Education - Joshi, Bishnu Maya; Acharya, Umesh; Koirala, Padma (NUTA Journal, 2023)
This study uses the quantitative methodology and cross-sectional study to examine the individual challenges faced by students in Open and Distance Learning (ODL) at Tribhuvan University's Faculty of Education. The research investigates the complexities of ODL, a flexible educational paradigm adopted by Tribhuvan University to reach diverse students. The study, conducted through a quantitative approach, examines challenges related to time management, financial constraints, unfavourable learning environments, limited interaction, and technical issues. It employs a Likert scale questionnaire and a cross-sectional design, with data collected from 145 respondents in May/June 2023. The findings reveal that ODL students encounter significant challenges in time management, financial constraints, and unfavourable learning environments. The digital divide and financial issues widen educational inequalities, posing obstacles for students from underprivileged and rural areas. The results underscore the multifaceted nature of challenges faced by ODL students, emphasizing the importance of tailored interventions. The analysis of socio-demographic variables indicates variations in challenges among different student groups, highlighting the need for inclusive support mechanisms. Despite gender-related differences being non-significant, variations in challenges based on caste/ethnicity, study programs, and other factors necessitate holistic strategies for improving the ODL experience. The study concludes with recommendations for addressing challenges, including bridging the digital divide, providing structured support for time management, and addressing financial barriers. Acknowledging and addressing these challenges is crucial for maximizing the transformative potential of ODL in higher education. The findings contribute valuable insights for educational institutions and policymakers aiming to enhance the ODL experience and ensure equitable access for diverse student populations.